(untitled) (Tribhuvan University Journal of Microbiology, 2019)
Objectives: This cross-sectional study was designed to detect the carbapenemase producing K. pneumoniae along with biofilm producers from different clinical specimens and to compare antibiotic susceptibility pattern of biofilm producing carbapenem resistant Klebsiella pneumoniae and biofilm non-producing carbapenem resistant Klebsiella pneumoniae. Methods: A total of 1475 non-repetitive clinical samples were included on this study. Antibiotic Sensitivity Testing (AST), Modified Hodge Test (MHT) and Modified Carbapenem inactivation method (mCIM) were performed for detection of carbapenemase production and Congo red agar method (CRA) along with Microtitre plate method were performed for detecting biofilm production. Results: Among the clinical specimens cultured, growth positivity was 62.71%. E. coli was most predominant organism followed by K. pneumoniae (17.89%). Among the 110 K. pneumoniae, 57 were found to be carbapenemase producer. Majority of the carbapenemase producing K. pneumoniae were isolated from sputum (45.61%), in the specimen collected from age group 61-70 (28.07%) and in out-patient department (50.88%). Similarly, 65.45% K. pneumoniae out of 110 were found to be biofilm producer by Congo red agar method while among those 72, 73.59% isolates were found to be quantitatively biofilm producer in Microtitre plate assay. Out of 57 carbapenemase producer, 35.08% were strongly biofilm producer while among 53 carbapenemase non-producer 30.18% were strongly biofilm producer from Congo red agar method. Moreover, Microtitre plate assay evidenced that, out of 57 carbapenemase producer, 40.35% were highly biofilm producing and among the 15 carbapenemase nonproducer 66.66% were highly biofilm producer. Conclusion: Biofilm formation is highly prevalent with varying degree of resistance among different antibiotics including carbapenems that further augments antibiotic resistance. The study showed carbapenemase producers are stronger biofilm producer than the non-carbapenemase producer. Therefore, it is recommended to identify biofilm formation among carbapenemase producers for effective choice of antibiotics.